Monitoring methods adapted to different perceptions and uses of functional biodiversity: Insights from a European qualitative study. (October 2021) - Cardona, Aurélie; Tchamitchian, Marc; Penvern, Servane; Dufils, Arnaud; Kramer Jacobsen, Stine; Korsgaard, Maren; Porcel, Mario; Świergiel, Weronika; Tasin, Marco; Warlop, François; Sigsgaard, Lene
Highlights: Lack of information about impact of farming practices on functional biodiversity. Diversity of perceptions and uses of functional biodiversity. Current indicators of functional biodiversity inadequate for a diversity of users. A guiding framework to adapt indicators to different objectives of farm management. Abstract: The role of functional biodiversity for favouring natural regulation and reducing pesticide use in fruit production is generally acknowledged. Although a number of farmers attempt to favour biodiversity through different strategies (e.g. diversified hedges, nesting boxes), they often lack means to evaluate how their actions contribute in practice to functional biodiversity. We assumed here that to create useful and appropriate monitoring methods, it is necessary to take into account the variety of knowledge, perceptions and interests about functional biodiversity. To test our hypothesis, we adopted a comprehensive and participative approach based on interviews and workshops with farmers, advisors and field agronomists involved in apple orchard management. Our objective was to understand their different perceptions and uses of functional biodiversity and then, to design monitoring methods adapted to those perceptions and pre-existing uses. Our findings revealed both a plurality of perceptions of functional biodiversity along with a diversity of objectives and uses of monitoring methods. Based on these results, we identified four main attitudes towards the management of functional biodiversity: the wait-and-see attitude, the naturalist attitude, the regulation attitude and the multifunctional attitude. These attitudes do not correspond to person's profiles, since one person can adopt different attitudes in regard to different biodiversity components or in regard to the different practices supporting biodiversity. In addition, attitudes can vary over time. The identification of these attitudes allowed us to design, with the workshops' participants, a guiding framework to create monitoring programs (i.e. combinations of monitoring methods) adapted to a variety of uses and targeted services.